2020
DOI: 10.1177/1362168820931897
|View full text |Cite
|
Sign up to set email alerts
|

Corrective feedback: Beliefs and practices of Vietnamese primary EFL teachers

Abstract: This study investigates Vietnamese EFL teachers’ beliefs and practices regarding oral corrective feedback, exploring and seeking to explain some of the relationships between beliefs and classroom practices. Data were collected in primary schools in Vietnam, and consist of 24 classroom observations and interviews with six teachers. Overall, the teachers showed high levels of awareness of the benefits of oral corrective feedback. They nominated pronunciation errors as the most important target for corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 61 publications
4
26
2
Order By: Relevance
“…On the other hand, rather than being influenced by concerns about students' affective responses to CF, the teachers in the present study showed some tensions between their overall objective of teaching, aiming to develop students' speaking competence in general, and fluency in particular, and the more practical objectives of the teaching and learning in their local contexts. Previous studies in teacher cognitions show that tensions and trade-offs between different sets of beliefs may lead to teachers' mismatches between their beliefs and practices (Phipps and Borg, 2009;Ha and Murray, 2020). It seems that, in the present study, the teachers' priority for helping students achieve good results in written exams which mainly tested students' knowledge of grammar and vocabulary exerts a stronger influence on their beliefs about CF targets than their aim to develop students' speaking fluency.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…On the other hand, rather than being influenced by concerns about students' affective responses to CF, the teachers in the present study showed some tensions between their overall objective of teaching, aiming to develop students' speaking competence in general, and fluency in particular, and the more practical objectives of the teaching and learning in their local contexts. Previous studies in teacher cognitions show that tensions and trade-offs between different sets of beliefs may lead to teachers' mismatches between their beliefs and practices (Phipps and Borg, 2009;Ha and Murray, 2020). It seems that, in the present study, the teachers' priority for helping students achieve good results in written exams which mainly tested students' knowledge of grammar and vocabulary exerts a stronger influence on their beliefs about CF targets than their aim to develop students' speaking fluency.…”
Section: Discussionmentioning
confidence: 49%
“…The protocol for the teachers' semi-structured interviews was developed based on the comprehensive review of recent CF literature (e.g., Lyster et al, 2013;Nassaji, 2016;Li, 2017;Ha and Murray, 2020). It was designed to elicit teachers' beliefs about various aspects of CF.…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As research in SLA has demonstrated the importance of CF provision (Ellis, 2017), the critical pedagogical questions of how, when, whom and what to best correct in L2 classrooms are worthy of further research (Ellis, 2017;Ha, 2017;Ha & Murray, 2020Lyster et al, 2013). As for investigations into students' preferences for CF types, the limited literature reveals some mixed findings.…”
Section: Students' Beliefs About Oral Corrective Feedbackmentioning
confidence: 99%
“…Among various aspects of CF research, CF beliefs have received the least research attention (Akiyama, 2017;Ha & Murray, 2020). Most of the research concerning learners' CF beliefs has included only a few questions probing students' opinions about the usefulness and necessity of CF as part of larger studies investigating other topics, predominantly beliefs about grammar instruction (Jean & Simard, 2011;Loewen et al, 2009;Schulz, 2001).…”
Section: Introductionmentioning
confidence: 99%